Digital Material Teaching: Learning Model and Learning Outcomes of Basketball - Silvy Juditya; Dhani Agusni Zakaria; Veny Juniarni Hardi; Sutiswo Sutiswo; Denok Sunarsi (Universitas Negeri Makassar, 2021)
The purpose of this study is to see the difference in influence between the personalized system of instruction (PSI) model based on digital teaching materials and the scientific model based on You Tube video. The research method used was an experiment with a pre test post test control group design, while the sample in this study were 160 students of SMPN 8 Cimahi, 80 students in the experimental group and 80 students in the control group. The research instrument used to measure basketball learning outcomes was in the form of a basketball basic motion skills test instrument (ITKGD BB). Analysis of the data used to process research data by using independent T-test analysis to see the difference in the effect of the two models on basketball learning outcomes. The results showed that the average value in the PSI group was 30.25, while for the scientific model group was 23.37, the t-count value was 11.696 with a significance level of 0.00 <0.005 (significant). Therefore, the conclusion in this study is that there is a difference in the influence between the personalized system of instruction (PSI) model based on digital teaching materials and the scientific model based on video you tube. It has an effect on basketball learning outcomes.